A comparison of sprint technique between professional football players and elite sprinters - Garden, C. A.; Tawiah-Dodoo, J.; Blenkinsop, G. M. (ISBS Proceedings Archive (Michigan), 2022)
This study compared sprint technique between professional footballer players and elite sprinters. Professional football players sprint technique was assessed using 2D video analysis and compared to publicly available data of elite sprinters from the IAAF biomechanical reports. Results showed sprinters had higher step frequencies and contacted the ground further back, with lower touchdown and higher toe-off distances.